2021
DOI: 10.1038/s41438-020-00431-9
|View full text |Cite
|
Sign up to set email alerts
|

SlGRAS4 accelerates fruit ripening by regulating ethylene biosynthesis genes and SlMADS1 in tomato

Abstract: GRAS proteins are plant-specific transcription factors that play crucial roles in plant development and stress responses. However, their involvement in the ripening of economically important fruits and their transcriptional regulatory mechanisms remain largely unclear. Here, we demonstrated that SlGRAS4, encoding a transcription factor of the GRAS family, was induced by the tomato ripening process and regulated by ethylene. Overexpression of SlGRAS4 accelerated fruit ripening, increased the total carotenoid co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(28 citation statements)
references
References 50 publications
1
22
0
Order By: Relevance
“…This epimutant revealed the potential relationship between epigenetic regulation and fruit ripening. Many TFs identified in the last two decades, such as HD-zip homeobox protein (LeHB-1), SlWRKY1, and SlGRAS4, regulate fruit ripening through a similar mechanism by directly binding to the promoters of ethylene biosynthesis genes and upregulating their transcripts [ 42 44 ]. SlARF2A and SlARF2B from the auxin response factor family act redundantly to regulate fruit ripening.…”
Section: Transcription Factors In Fruit Ripeningmentioning
confidence: 99%
“…This epimutant revealed the potential relationship between epigenetic regulation and fruit ripening. Many TFs identified in the last two decades, such as HD-zip homeobox protein (LeHB-1), SlWRKY1, and SlGRAS4, regulate fruit ripening through a similar mechanism by directly binding to the promoters of ethylene biosynthesis genes and upregulating their transcripts [ 42 44 ]. SlARF2A and SlARF2B from the auxin response factor family act redundantly to regulate fruit ripening.…”
Section: Transcription Factors In Fruit Ripeningmentioning
confidence: 99%
“…Ethylene is a crucial phytohormone involved in plant responses to biotic stress as well as in tomato fruit development (Liu et al, 2021). In tomato, ethylene is induced by the pathogenic fungus Oidium neolycopersici (Kissoudis et al, 2016) and by P. syringae pv.…”
Section: The Tomato Response To Edna Is the Modulation Of Receptor-like Protein Kinases And Ethylene-responsive Factorsmentioning
confidence: 99%
“…Tomato GRAS1 is also differentially expressed in breaker and mature fruits emphasizing its role in fruit development ( Huang et al., 2015 ). Recently, it has been demonstrated that a GRAS TF, SlGRAS4, was involved in tomato ripening by regulating ethylene biosynthesis genes and MADS TFs ( Liu et al., 2021 ). SlGRAS4 binds to the promoter sequence of the crucial ethylene biosynthesis genes (like SlAC O 1 and SlAC O 3 ), activates their expression, and enhances the fruit ripening.…”
Section: Biological Functions Regulated By Grasmentioning
confidence: 99%